Anatomic variation of the entrance of the optic canal into the orbit. (4th July 2019) - Ugradar, Shoaib; Goldberg, Robert; Rootman, Daniel
ABSTRACT: Purpose : To characterise variations in the location of the optic canal and its entry into the orbit in relation to the sphenoid sinus. Methods : In this observational study, patients with high-resolution computed tomography (CT) scans seen by 2 specialists (RG and DR) over a period of 12 years were reviewed for study entry. The primary outcome measure was characterisation of the optic canal route in relation to the sphenoid sinus and the location of its opening within the orbit. Three-dimensional reconstructions of the bony orbits were created using the Mimics imaging software. Optic canals were classified according to the location of their entry into the orbit. Type 1 was defined as a canalicular course along the lateral wall of the sphenoid sinus and entry into the orbit through the medial wall. Type 2 was defined as a canalicular course in the superior wall of the sphenoid sinus with entry into the orbit through the roof. The angle of entry of each nerve into the orbit was calculated. Results : One-hundred patients (52 females and 48 males) contributed 100 orbits to the study. Type 1 configuration was noted in 90 orbits, whereas Type 2 was noted in 10 orbits. The mean angle (SD) of entry of Type 1 optic nerves into the orbit was 61° (10.7), whereas the angle of entry of Type 2 nerves was 32.35° (6.8). The difference was significant ( p < 0.01). Conclusions : This study demonstrates variability of the path and outlet of the optic canal and presents a relatively common (10%) configuration in which the optic canal travels in the roof of the sphenoid sinus rather than the expected position in the lateral wall.